(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
Language is a tool for negotiating power, and every use of language exhibits this feature. More so is the use of language on a platform that reaches millions of people and is recurrent enough to become part of the repertoire of knowledge of a people, whether consciously or unconsciously, as it often occurs in popular pop songs in Nigeria. The case of Zazoo Zehh by Portable, featuring Olamide and Pocolee, is assessed in this study. The song and its music video are subjected to the methods of critical discourse analysis from a multimodal perspective to identify the features of the use of language in the song and its video, which project the ideologies of the musicians and how power is negotiated in the lyrics. Norman Fairclough’s socio-cognitive approach to CDA is adopted for the CDA aspect of the study while social semiosis accounts for the modes available in the data. Findings show a firm assertion of power which is then used to indoctrinate followers into traits and characters that are more evident in society today. These support the speculation that songs like Zazoo Zehh propagate some negative traits among the youth, and language use tends to ascribe some perceived power to those who sing them. It is thus suggested that mechanisms be put in place for stronger censorship to protect the young members of society.